On the optimal cathode catalyst layer for polymer electrolyte fuel cells: Bimodal pore size distributions with functionalized microstructures - García-Salaberri, Pablo A.; Sánchez-Ramos, Arturo; Das, Prodip K. (Frontiers in Energy Research, 2022)
A high advancement has been achieved in the design of proton exchange membrane fuel cells (PEMFCs) since the development of thin-film catalyst layers (CLs). However, the progress has slowed down in the last decade due to the difficulty in reducing Pt loading, especially at the cathode side, while preserving high stack performance. This situation poses a barrier to the widespread commercialization of fuel cell vehicles, where high performance and durability are needed at a reduced cost. Exploring the technology limits is necessary to adopt successful strategies that can allow the development of improved PEMFCs for the automotive industry. In this work, a numerical model of an optimized cathode CL is presented, which combines a multiscale formulation of mass and charge transport at the nanoscale (∼10nm) and at the layer scale (∼1μm). The effect of exterior oxygen and ohmic transport resistances are incorporated through mixed boundary conditions. The optimized CL features a vertically aligned geometry of equally spaced ionomer pillars, which are covered by a thin nanoporous electron-conductive shell. The interior surface of cylindrical nanopores is catalyzed with a Pt skin (atomic thickness), so that triple phase points are provided by liquid water. The results show the need to develop thin CLs with bimodal pore size distributions and functionalized microstructures to maximize the utilization of water-filled nanopores in which oxygen transport is facilitated compared with ionomer thin films. Proton transport across the CL must be assisted by low-tortuosity ionomer regions, which provide highways for proton transport. Large secondary pores are beneficial to facilitate oxygen distribution and water removal. Ultimate targets set by the U.S. Department of Energy and other governments can be achieved by an optimization of the CL microstructure with a high electrochemical surface area, a reduction of the oxygen transport resistance from the channel to the CL, and an increase of the catalyst activity (or maintaining a similar activity with Pt alloys). Carbon-free supports (e.g., polymer or metal) are preferred to avoid corrosion and enlarge durability.